Improving the quality of financial statements and the survival of MSMEs through digital economy: The case of Indonesia and Malaysia - Ratna Komala, Adeh; Firdaus, Dony Waluya (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This research aims to assess how much the digital economy influences the quality of financial statements and the survival of MSMEs in Indonesia and Malaysia. This research used an analysis unit of 201 MSMEs registered in the Indonesian Chamber of Commerce and Industry and a literature review on the digital economy of MSMEs in Malaysia. The analytical approach was then utilized to examine validity, reliability, classical assumptions, analysis path, and hypothesis testing using the t-test in SPSS version 23.0. The results of hypothesis testing in this research show that the digital economy affects the quality of financial statements and has a unidirectional relationship with strong categories. These findings suggest that the digitalization of the economy is critical for MSMEs because it lowers operational costs and exposes them to a broader range of potential customers. Like Indonesia, Malaysia is also concerned about MSMEs' business sustainability, which inspired them to achieve the goal of making Malaysia the center of economic digitalization. This goal would involve technological advances, indicating that MSMEs in Indonesia and Malaysia can improve their financial gain through digital transformation.